Recursive Economy and Policy Innovation in Indonesia’s Post-Resource Economy - Arina Romarina; Ardieansyah Ardieansyah; Lalu Satria Utama; Elvira Mulya Nalien; Bima Eka Putra; Marimbi Liebe Na’illah Dida; Biva Aditya Yuda Makatara; Luthfi Azhari (Pattimura University, 2026)
Indonesia’s economy has long relied on non-renewable natural resources, which are now depleting, posing risks to long-term economic stability. The transition to a recursive economy—where resources are continuously reused and innovation drives sustainability—is critical. However, the role of policy innovation in facilitating this shift remains underexplored, particularly in integrating green economy principles, fiscal governance, and Just Energy Transition (JET) frameworks. This study examines how innovative policies can accelerate Indonesia’s transition to a recursive, post-resource economy. It fills a gap in literature by linking green government initiatives (e.g., fiscal incentives, R&D capacity) with economic resilience, while incorporating JET as a key variable. The novelty lies in synthesizing governance, technology, and diversification strategies into a unified policy model for sustainable transition. A Systematic Literature Review (SLR) is employed, analyzing peer-reviewed articles, government reports, and international case studies (2010–2025) on green economy transitions. Data is thematically coded to identify policy patterns, technological drivers, and institutional barriers. Findings reveal that: (1) Fiscal policies (e.g., carbon taxes, green subsidies) significantly boost renewable energy adoption; (2) Strong R&D investment correlates with faster industrial diversification; (3) JET-aligned governance enhances equity in transition outcomes. However, bureaucratic fragmentation and short-term economic priorities hinder progress. To achieve a recursive economy, Indonesia must: (1) Integrate green fiscal policies with JET commitments; (2) Strengthen cross-sectoral R&D collaboration; (3) Institutionalize metrics for long-term resilience. Recommendations include piloting circular industrial zones and aligning regional governance with national green targets.